The Teacher's Efforts In Creating Child Friendly Classrooms 4-5 Years Old With Anti-Bullying Talking Box Media In Baitul Aziz Kindergarten - Nur Hamidah (Yayasan Rahmat Islamiyah, 2023)
This research is motivated by acts of bullying that have recently occurred in school environments, with this the government provides child-friendly school solutions. Child-friendly schools or a simpler scope of child-friendly classes. To create a child-friendly class that fills a safe, comfortable and fun place for students, the teacher plays a very important role in creating a child-friendly class. The focus of the research in this paper is how the teacher's efforts in creating a friendly class for children aged 4-5 years using anti-bullying talking box media in Baitul Aziz Kindergarten. The purpose of this study was to find out how the teacher's efforts in creating child-friendly classes with anti-bullying box media. This research method uses a qualitative approach with a descriptive type, namely to describe the teacher's efforts in creating child-friendly classes with anti-bullying talking box media using observation, interview and documentation data collection techniques. The results of the study show that the teacher's efforts to create child-friendly classes are: a) through classroom learning, through prayer before and after learning, informing acts of bullying, giving direct examples. b) through activities outside the classroom, shaking hands with peers and teachers, praying Duha, reminding bad words and deeds. c) through the anti-bullying talk box media.